A Bioinformatics Guide to Plant Microbiome Analysis - Lucaciu, Rares; Pelikan, Claus; Gerner, Samuel M.; Zioutis, Christos; Köstlbacher, Stephan; Marx, Harald; Herbold, Craig W.; Schmidt, Hannes; Rattei, Thomas (Frontiers in Plant Science, 2019)
Recent evidence for intimate relationship of plants with their microbiota shows that plants host individual and diverse microbial communities that are essential for their survival. Understanding their relatedness using genome-based and high-throughput techniques remains a hot topic in microbiome research. Molecular analysis of the plant holobiont necessitates the application of specific sampling and preparatory steps that also consider sources of unwanted information such as soil, co-amplified plant organelles, human DNA and other contaminations. Here we review state-of-the-art and present practical guidelines regarding experimental and computational aspects to be considered in molecular plant-microbiome studies. We discuss sequencing and ‘omics’ techniques with a focus on the requirements needed to adapt these methods to individual research approaches. The choice of primers and databases are of utmost importance for amplicon sequencing while the assembly and binning of shotgun metagenomic sequences is crucial to obtain quality data. We discuss specific bioinformatic workflows to overcome the limitation of genome database resources and for covering large eukaryotic genomes such as fungi. In transcriptomics, it is necessary to account for the separation of host mRNA or dual-RNAseq data in while metabolomics offers a powerful tool to detect and quantify small molecules and molecular changes at the plant-bacteria interface if the necessary requirements with regard to (secondary) metabolite databases are considered. Metaproteomics approaches provide a snapshot of the protein abundances within a plant tissues which requires the knowledge of complete and well-annotated plant genomes as well as microbial genomes. We highlight data integration and complementarity which should help to widen our understanding of the interactions among individual players of the plant holobiont in the future.